THE EFFECT OF SOCIAL AND CIVIC VALUES ON ACCOUNTING STUDENTS' ACCOUNTABILITY ATTITUDES AT THE FACULTY OF ECONOMICS, HKBP NOMMENSEN UNIVERSITY, MEDAN - Rince Rince; Harningsih Fitri Situmorang (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
s study aims to examine and analyze the influence of social values and citizenship values on the accountability attitude of accounting students at the Faculty of Economics, HKBP Nommensen University. Accountability reflects a moral and ethical attitude that demonstrates an individual's responsibility to perform tasks honestly, transparently, and reliably. In the context of higher education, the development of student accountability is influenced by various factors, including social values and citizenship values that are instilled through learning processes and campus life. This research employs a quantitative approach with an associative method. The population of the study consists of all students of the Accounting Study Program, Faculty of Economics, HKBP Nommensen University. The sample was determined using a proportional random sampling technique, totaling 133 respondents. Data were collected through a closed-ended questionnaire and analyzed using multiple linear regression with the assistance of the latest version of SPSS software. The results indicate that social values have a positive and significant effect on students' accountability attitude. Likewise, citizenship values also have a positive and significant influence on accountability. Simultaneously, both variables contribute significantly, explaining 62.4% of the variation in students' accountability attitudes. This finding implies that the higher the students' social and citizenship values, the stronger their accountability behavior in both academic and social contexts. In conclusion, the formation of accountability attitudes among accounting students is influenced not only by cognitive aspects but also by the internalization of strong social and citizenship values. Therefore, universities need to strengthen character-based and civic education activities to develop accounting graduates who are both professional and highly ethical..